Analysis of Current Trends in Antisemitism - ACTA (De Gruyter Oldenbourg, 2018)
The ACTA papers focus on contemporary trends of antisemitism world-wide. The eJournal allows for a prompt publication of contributions that analyze current phenomena of antisemitic prejudice, occurrences, and mechanisms. It is a platform for innovative, cutting-edge research. Adopting a transdisciplinary approach, they scrutinize the singularities of anti-Jewish prejudice with relation to and in the context of other forms of discrimination.